2023
DOI: 10.3389/fneur.2023.1164604
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of acupuncture on sleep quality for post-stroke insomnia: a systematic review and meta-analysis

Abstract: BackgroundStroke is the second leading cause of death worldwide, and improving sleep quality in post-stroke insomnia is beneficial to the recovery of stroke. Acupuncture is widely used for the treatment of post-stroke insomnia in China. Therefore, this systematic review and meta-analysis were performed to explore the efficacy and safety of acupuncture for post-stroke insomnia.MethodsEight databases were searched from their inception to 12 September 2022. Two reviewers independently performed the study screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Multiple randomized controlled trials have shown that acupuncture serves as a useful tool for patients with post-stroke sleep disorders [225][226][227]. Recently, acupuncture therapy, as a traditional Chinese medicine therapy, has been widely used in the treatment of post-stroke sleep disorders for its convenient operation and low adverse effect characteristics [228][229][230][231].…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%
“…Multiple randomized controlled trials have shown that acupuncture serves as a useful tool for patients with post-stroke sleep disorders [225][226][227]. Recently, acupuncture therapy, as a traditional Chinese medicine therapy, has been widely used in the treatment of post-stroke sleep disorders for its convenient operation and low adverse effect characteristics [228][229][230][231].…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%